1994
DOI: 10.1002/jsfa.2740660316
|View full text |Cite
|
Sign up to set email alerts
|

Effects of conditioning factor on anthocyanin production in strawberry suspension cultures

Abstract: To investigate the effects of the conditioning factor on anthocyanin production in the cultured strawberry, Fragaria ananassa cv Shikinari, cells were cultured in LS medium supplemented with a filtered conditioned broth. Anthocyanin accumulation was greatly enhanced using media conditioned for 5-8 days. This effect was promoted by increased concentrations of the conditioned broth. The amount of anthocyanin produced in a 100% conditioned broth was about eight times higher than in the control broth after 5 days.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
1
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(7 citation statements)
references
References 27 publications
1
4
1
1
Order By: Relevance
“…3a) differed slightly from the results obtained in the former experiment (Mori et al,1994b), however, the same tendency was observed.…”
Section: Changes In Anthocyanin Compositioncontrasting
confidence: 55%
See 2 more Smart Citations
“…3a) differed slightly from the results obtained in the former experiment (Mori et al,1994b), however, the same tendency was observed.…”
Section: Changes In Anthocyanin Compositioncontrasting
confidence: 55%
“…While Stuart and Street (1969) used filtered cultured medium of Acer pseudoplatanus as the conditioned medium to stimulate cell growth, we have also reported increased anthocyanin production using conditioned medium (Mori et al, 1994b). In the report, we revealed that anthocyanin synthesis is increased according to the concentration of the added conditioned medium which was subcultured 1. week under 800 lux.…”
Section: Introductionsupporting
confidence: 50%
See 1 more Smart Citation
“…조정배지는 세포를 회수하고 남은 배양액으로 세포로부터 분비된 글루코오스, 아미노산, 핵산과 같은 대사산물, 인터루 킨, EGF (epidermal growth factor)와 같은 성장인자 그리고 세 포 외 기질 단백질 등을 포함하고 있다 [12,13]. 또한 세포는 배양하는 도중 세포 내에 포함되어 있던 다양한 조정성분들 을 배지 내로 방출하며 배지 내 환경을 생장에 적절한 형태로 바꾸어 증식하게 된다 [14,15]. 여기서 조정성분들은 세포 간 의 상호작용이 가능하도록 배출되는 일종의 신호물질이다 [16,17].…”
Section: Introductionunclassified
“…Anthocyanins have been produced in various plant tissue cultures (Mori et al, 1993). Their production is strongly influenced by factors such as light exposure (Takeda, 1988), plant growth regulators (Ozeki and Komamine, 1986;Mori et al, 1994a), high sucrose concentration (Yamakawa et al,1983;Yamamoto et al, 1989), UV (Wellman et al, 1976), nitrogen sources (Do and Cormier, 1991a,b), types of sugar (Nakajima et al, 1989), osmotic stress (Do and Cormier, 1991c) and conditioning factors (Mori et al, 1994b).…”
Section: Introductionmentioning
confidence: 99%